Current Topics and Emerging Issues in Malaria Elimination - Rodriguez-Morales, Alfonso J. (Infectious Diseases, 2021)
Malaria is one of the most important tropical diseases in the history of the world. This vector-borne disease has been a significant cause of morbidity and mortality in tropical countries of Africa, Asia, and Latin America. As such, this book provides updated information on epidemiological and public health research of malaria conducted in the last decade. Over four sections, chapters discuss such topics as diagnosis, epidemiology and surveillance, policy and prevention, and vector control and vaccines.